Social thought about infancy: A sociohistorical view from the Global South - Jaramillo, Enrique (2018)
The present work presents some ideas to understand and explain the configuration of discourses and social representations in the history of social thought about infancy, stemming from the violent and brutal occidental invasion, colonization, and the imposition of a pattern of hierarchical and authoritarian power in the infancy and family of indigenous and blacks, in the process of coloniality of power and knowledge. Notwithstanding that, there are two cultural knots in dispute with regards to infancy: the rationale of native cultures from the Global South, and the occidental rationale that was consolidated with the social pact of modernity in the 18th Century, lasting until our days.